Criteria for spin instability based on the node distribution in Trace-transform of the SHS combustion wave chronogram. Issue 1 (February 2021) - Grigoryevskaya, A; Gulyaev, P; Jordan, V; Shmakov, I
Abstract: The article presents the results of the Trace analysis of three types of experimental chronograms of the SHS combustion wave in ignition, extinction, and stable propagation modes. It is shown that the use of the differential chronoscopy (DCS) method allows one to reliably determine the moment of occurrence of the spin instability of the SHS wave by the presence of local maxima of the T-functional, when the trace line exactly coincides with the image of the combustion wave front on the DCS map. It was found that in the stable spin combustion mode, the DCS map is a set of periodic isoclines, and this leads to the appearance of point nodes in the 2D image of the Trace transform. As a criterion for recognizing spin instability, we selected the feature of the appearance of local maxima in the central transverse region of the Trace transform spectrum. It is concluded that spin instability is characteristic of the transition from thermal to diffusion instability in the presence of a hysteretic dependence of the burning rate on temperature.